POLA DAN STRATEGI MANAJEMEN BERBASIS SEKOLAH DALAM MENGHADAPI PERSAINGAN MUTU - Muhammad Isnaini (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2012)
The debate over how Centralized or decentralized the Management of Education System Should be is essential to the Success of Strategies for Improving or reforming the System. One of the main Aims of Educational reform and Probably the best means of Going about it is to involve the Stakeholders in Decision making. There are Varieous aspects to School’s autonomy. It applies first to resource managements it means that the school should be able to decide how to use a substantial portion of it Alloted resources. Many reasons have bean advanced to explain why this should be, but accordingly school based management it way for forching Individual school to take responsibility for what happens to childrens under Their jurisdiction and attending their school. It should be so, becouse school as Institutions is the specific set essential function is serves in our society. So that, school based management should be understood as policy problem which needs problem structuring. Policy alternatives, hypothetical recommendation about policy output, policy actions, outcomes and Consequencies. To more about its functions it accordance at education setting of Indonesia today. The Writer will have at last partialy fulfiled as below.